2017
DOI: 10.4172/2161-1122.1000427
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Microleakage, Surface Roughness and Hardness of Three Glass Ionomer Cements – Zirconomer, Fujii IX Extra GC and Ketac Molar: An In Vitro Study

Abstract: Objective: To compare and evaluate microleakage, surface roughness and hardness of three glass ionomer cements -Zirconomer, Fujii IX Extra GC and Ketac Molar. Materials and methods:For microleakage evaluation, 150 extracted human maxillary permanent first premolars were randomly divided into five groups of 30 teeth each. Standardized class V cavity preparation was done on the buccal surface of all the groups except group 1. In group 2, cavity was prepared but left unrestored. Group 3, 4 and 5 were restored wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 17 publications
5
19
0
2
Order By: Relevance
“…This is comparable to previous studies that reported Zirconomer showing higher microleakage scores as compared to composite and amalgam in class I cavities of non-carious permanent molars (30). Another study reported that Zirconomer had a higher microleakage as compared to nano-ionomer in class V cavities of noncarious premolars (22).…”
Section: Discussionsupporting
confidence: 86%
“…This is comparable to previous studies that reported Zirconomer showing higher microleakage scores as compared to composite and amalgam in class I cavities of non-carious permanent molars (30). Another study reported that Zirconomer had a higher microleakage as compared to nano-ionomer in class V cavities of noncarious premolars (22).…”
Section: Discussionsupporting
confidence: 86%
“…A recent study by Asafarlal ( 26 ) investigated the microleakage of three different GICs-Zirconomer, Fuji IX Extra and Ketac Molar quantitatively. After immersion the teeth individually in 0.5% methylene blue dye for 24 hr, the samples were dissolved in 2ml of 65% nitric acid, the solutions were centrifuged and then spectrophotometer was used to assess the dye penetration.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the dye concentration in the experimental solutions showed that the microleakage value of Zirconomer was higher compared to the other GICs. This was believed to be owing to large size of the filler particles of zirconia which leading to poor adaptation at the tooth-restoration interface ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous research on marginal leakage of Zirconmer and highly viscous GI, the sealing ability of highly viscous GI was much better than Zirconomer. This was thought due to presence of large sized Zirconia particles in Zirconomer that hinders its good adaptation to the tooth surface (13) .…”
Section: Discussionmentioning
confidence: 99%